The two Revolutions in Economic History - Martina Cioni; Giovanni Federico; Michelangelo Vasta (European Historical Economics Society (EHES), 2020)
This paper compares the Cliometric Revolution, which transformed economic history in the 1960s, with the current developments in the field with a quantitative analysis based on two databases, totalling more than 3,500 articles. We show that the share of Cliometric articles in the top three economic history journals increased from 1958 to 2000 more slowly than some ex-post narratives lead to believe. We outline the developments from 2001 to 2019 by looking at economic history articles published in the top five field economic history journals and in thirteen prominent economics journals. Most articles in these latter deal with economics of the past ('traditional cliometric'), but quite a few put forward a revolutionary change in the research questions. The 'persistence studies' (PS) look for the historical origins of current outcomes, the 'non-economic outcomes studies' (NEOS) extend the issues well beyond the traditional boundaries of economics, towards sociology, anthropology and above all political science. This Second Revolution was started by young economists who published in some of the top economics journals following the seminal article by Acemoglu, Johnson and Robinson (2001). We show that some PS have had on average a huge impact in terms of citations and that they have been more successful than the NEOS. We conclude with some musings about the future of economic history. There might be a new synthesis, with scholars integrating a wider range of research questions, 'traditional cliometric', PS and NEOS. Or perhaps the field will splinter in three independent research streams.
Keywords: N01; 330; Cliometric Revolution; Citational success; Economic history journals; Persistence studies